Study of adverse drug reactions associated with antiepileptic drugs: a pharmacovigilance study using spontaneous reporting system - Mukhyaprana, Sudha K.; Devipriya, Siddiraju; Thirumalaiappan, Meenakshi (International Journal of Basic & Clinical Pharmacology, 2021)
Background: More than 25 antiepileptic drugs (AEDs) are available in the Indian market to treat epilepsy of which many have similar efficacy but differ in their tolerability and are associated with many adverse drug reactions (ADRs). ADRs are one of the most common causes of death and clinical trials are not sufficient to uncover all the ADRs, hence post-marketing surveillance or pharmacovigilance is necessary. The aim of the study was to analyze the ADRs of AEDs by spontaneous reporting system under Pharmacovigilance Program of India (PvPI). Methods: Suspected ADR reporting forms provided by PvPI were used to collect the data from healthcare professionals of Madras Medical College and Rajiv Gandhi Government General Hospital, Chennai. Results: A total of 77 ADRs from 61 reports were analysed of which 34 were male and 27 were female patients and maximum were in the middle-aged adult group (N=44). Majority of the ADRs were related to skin and subcutaneous disorders (N=55) and most implicated ADR was found to be maculopapular rash (N=12) associated with phenytoin. Most of the ADRs were non-serious (N=42) and were probable category (N=45) as per WHO-UMC scale. Conclusions: Monitoring ADRs in patients using antiepileptic drugs is a matter of importance; hence a robust pharmacovigilance practice is essential.